1991
DOI: 10.1159/000261336
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Distribution Patterns of Surface ‘Prismless’ Enamel in Human Permanent Teeth

Abstract: Using human permanent teeth, structural and distribution patterns of the surface ‘prismless’ enamel with the occasional presence of indistinct and/or stunted prism structures were investigated by scanning electron microscopy. The ‘prismless’ enamel was classified into three shapes: step-like, occurring in mid-coronal enamel; band-like, frequently seen in occlusal and fissure enamel, and island-like, found in occlusal and cuspal-coronal enamel. These three ‘prismless’ shapes were formed by two structural patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 15 publications
4
52
0
Order By: Relevance
“…All teeth were from per sons who had been living in an area with fluoridated water (1 ppm F). But because a natural, nonpolished enamel sur face is known to have irregularities in its structure [Whittak er, 1982;Fejerskov et al, 1984;Kodaka et al, 1991], the sur face variations observed are understandable. It would have been impossible to evaluate the degree of erosion on the basis o f the scanning electron microscopic pictures alone.…”
Section: Scanning Electron Microscopical Findingsmentioning
confidence: 99%
“…All teeth were from per sons who had been living in an area with fluoridated water (1 ppm F). But because a natural, nonpolished enamel sur face is known to have irregularities in its structure [Whittak er, 1982;Fejerskov et al, 1984;Kodaka et al, 1991], the sur face variations observed are understandable. It would have been impossible to evaluate the degree of erosion on the basis o f the scanning electron microscopic pictures alone.…”
Section: Scanning Electron Microscopical Findingsmentioning
confidence: 99%
“…The specimens were finally polished with 5-and 0.3-,um alumina on polishing cloths in order to expose the outer 300 500 pm deep enamel layers, so that the layers would contain low fluoride levels [Weathered et al, 1983;Luoma et al. 1986] and no prismless enamel [Whittaker, 1982;Kodaka et al, 1990Kodaka et al, , 1991, The specimens were cut into about 5x5-m m enamel areas (25 mm2), 2 mm thick and etched with 30% phosphoric acid at pH 1.4 for 60 s after ultrasonic cleaning. Sixteen samples were randomly divided among the 4 subjects with each group of four samples attached to a resin plate with simple clasps for each subject.…”
Section: Preparation O F Specimensmentioning
confidence: 99%
“…However, the structure of enamel is not homogeneous; the initial layer at the dentino-enamel junction (DEJ), and particularly the final, superficial layer at the enamel surface, is structurally distinct from inner (bulk) enamel. Inner enamel is characterized by the parallel arrangement of long apatite crystals within decussating prisms (layered in alternate directions), while outer enamel appears as a relatively thin region where enamel prisms display a honeycomb pattern in both rodents Risnes et al, 1996] and humans [Kodaka et al, 1991]. Subsequent to this, a very thin layer of prismless final enamel is deposited at the enamel surface within which the enamel crystals generally run perpendicular to the tooth surface.…”
Section: Introductionmentioning
confidence: 99%